Multilayer Polymeric Nano composite Membrane for Oxygen Separation - Nallathambi, Gobi; Dhinakaran, Hazel (Bulletin of Scientific Research, 2019)
Air separation is a process of separating primary components from the atmospheric air. Development of membrane technologies plays a key role in air separation. Multi-layer polymeric nanocomposite membranes have been developed by a novel technique using Polyacrylonitrile (PAN) and cellulose acetate (CA) along with nano silica particles (SiO2) to obtain a higher oxygen selectivity and permeability. For the construction of the multilayer membrane, the Box-Behnken design has been used by employing three independent variables namely PAN Electro spinning time, the SiO2 percentage in the PAN polymer and CA/PEG polymer concentration. The developed membranes have been characterized for its surface morphology and physical properties. Along with the analysis of compound desirability, the results were also subject to statistical analysis in order to form regression equations. The electro spun fiber diameter increases along with the concentration of SiO2 nanoparticles and the range is from 50 nm to 400 nm. Moreover, the maximum pore size on the surface of the membrane lies between 200 to 400 nm whereas the maximum percentage of oxygen purity obtained is 48 with the permeate flux of 5.45 cm3/cm2/min.